The Use Of Homonyms Words In Top 5 Tongue Twister English- Learn English With English Class - I Gede Neil Prajamukti Wardhana; Gina Ivana Mambrasar; Ni Luh Desy Suari Dewi; Gek Wulan Novi Utami (Denpasar Institute, 2023)
The purpose of the study is to determine the types of homonymous words and the meaning of each type of homonymous word in the top 5 Tongue twister English- learn English with English class on the YouTube channel Learning English. The data was analyzed using Parera's (2004) theory. The research design is qualitative, and the data sources for this investigation are the homonyms that appear within the tongue twister. According to the data, there are two types of homonyms: homophones and homographs. There are ten homophones on the video, two in each tongue twister, while there is only one homograph in the